Inocuidad y bioconservación de alimentos - de la Fuente Salcido, Norma Margarita; Barboza Corona, José Eleazar (Acta Universitaria, 2010)
People are interested in consuming free pathogen foods that contains low amount of chemical additives, with acceptable sensorial properties and nutritionally rich to representan alternative to disease prevention. In this work, we analyzed not only the importance toconsume innocuous food but also the different ways of food preservation through bacterial proteins called bacteriocins. In particular, the bio-preservation of dairy, meat, marine and vegetable products is reviewed. Finally, the importance of water in food preservation and the form to increment the bacterial susceptibility to antimicrobial agents applying the hurdle technology is discussed.
Keywords: Array; Array; Array